Mnenje uporabnikov o učinku podpražne električne stimulacije na spastičnost in funkcijo zgornjega uda pri otrocih in mladostnikih z okvaro osrednjega živčevja - Kostanjšek, Laura (Rehabilitacija (Ljubljana), 2022)
Introduction: Various therapeutic methods are used to improve arm function in children with central nervous system impairment, including subthreshold electrical stimulation. We were interested in what experiences children and adolescents have of using the latter. Methods: We invited 15 children and adolescents who were included in the rehabilitation program in the period from 2017 to 2021 after a brain injury. To reduce spasticity, we fitted them with a mesh-glove for sub-threshold electrical stimulation, which was used in the home environment. Twelve of them responded to the invitation, with an average age of 14.6 years. To evaluate users experience and opinions on possible effects, we prepared a questionnaire. Results: The majority of children and adolescents used the glove regularly, almost every day, for half an hour on average. Less pronounced spasticity and better hand function have been reported. Only a few reported negative effects of stimulation associated with skin changes. Conclusion: With the help of a questionnaire, we gained insight into the experience of using mesh-glove in children and adolescents. For a quantitative analysis of its effectiveness, it will be necessary to develop a precise protocol of use and select baseline variables, ranging from the impact on spasticity to the impact on performance and cooperation.
Keywords: Adolescent; cerebral palsy; cerebralna paraliza; Child; hand; mesh-glove; mladostnik; mrežasta rokavica; otrok; podpražna električna stimulacija; roka; subthreshold electric stimulation; therapy; Upper Extremity